“Parallel reforms and double efforts”: Latvia`s experience reforming administration - Reinholde, Iveta (Socialiniai tyrimai, 2014)
The public administration reform process in Latvia from the beginning of the 1990s was separated into two parts - national administrative reform and administrative territorial reform – both with their own unique goals and implementation mechanisms. The divided coordination and management of the reforms have resulted in the two administrative subsystems. The paper’s aim is to explore the links between reforms in the national level and local level after 2004 by analyzing the main reform documents determining all reform activities at that time. The results will demonstrate the complexity of the reform management process, as the coordination of reforms is essential regarding all of its levels and sectors.
Keywords: reforms; modernisation; public administration; local municipalities